El error y la errancia: el pirata «luterano» épico en las Indias - Lise Segas (Les Cahiers de Framespa)
At the turn of the 17th century, English privateers assaulted Spanish West Indian coasts and cities, from the Mar del Norte to the Mar del Sur. This enemy, religious and foreign, the «pirata luterano», became at that time a «two-face» epic hero in the Spanish-American epic poetry cycle: he aroused both the admiration of his contemporaries and at the same time the most severe condemnation for his subversive actions and discourses. This new coastal war that rages is the heart of the poetic narrative of the texts studied here and is also at the origin of a larger and cloaked reflection about colonial society and the role of arms in the Spanish Imperial project.